The price of flexibility – a case study on septanoses as pyranose mimetics. Issue 3 (17th November 2017) - Sager, Christoph P.; Fiege, Brigitte; Zihlmann, Pascal; Vannam, Raghu; Rabbani, Said; Jakob, Roman P.; Preston, Roland C.; Zalewski, Adam; Maier, Timm; Peczuh, Mark W.; Ernst, Beat
Abstract : Interacting with lectins, mannose can be mimicked with seven-membered ring analogues but at the price of a substantial entropy penalty. Abstract : Seven-membered ring mimetics of mannose were studied as ligands for the mannose-specific bacterial lectin FimH, which plays an essential role in the first step of urinary tract infections (UTI). A competitive binding assay and isothermal titration calorimetry (ITC) experiments indicated an approximately ten-fold lower affinity for the seven-membered ring mannose mimetic 2- O-n -heptyl-1, 6-anhydro-d - glycero -d -galactitol (7 ) compared to n -heptyl α-d -mannopyranoside (2 ), resulting exclusively from a loss of conformational entropy. Investigations by solution NMR, X-ray crystallography, and molecular modeling revealed that7 establishes a superimposable H-bond network compared to mannoside2, but at the price of a high entropic penalty due to the loss of its pronounced conformational flexibility. These results underscore the importance of having access to the complete thermodynamic profile of a molecular interaction to "rescue" ligands from entropic penalties with an otherwise perfect fit to the protein binding site.